The Influence of Brand Image on Purchasing Decisions at Bakso Boejangan Kuta Branch, Bali - Kurniadewi, Ni Kadek; Pranadewi, Putu Mira Astuti; Juniari, Ni Kadek Eni (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study is based on the phenomenon of the increasing number of meatball culinary businesses with various types of services offered. This study aims to examine the Influence of Brand Image on Purchasing Decisions at Bakso Boedjangan, Kuta, Bali branch. The study consists of two variables, namely brand image (X) and purchasing decision variables (Y). The indicators used in measuring brand image are the superiority of brand associations, the strength of brand associations and the uniqueness of brand associations. And the indicators used in measuring purchasing decisions are cultural factors, social factors, personal factors, and psychological factors. The results of the partial analysis show that there is a significant positive influence individually on brand image variables on purchasing decisions, which means that the better the brand image, the better the decision to purchase Bakso Boedjangan, Kuta, Bali branch.